2003
DOI: 10.1111/1467-7660.00325
|View full text |Cite
|
Sign up to set email alerts
|

Globalization and the Urban Property Boom in Metro Cebu, Philippines

Abstract: The hyper mobility of capital and the associated growth of international investment in real estate which occurred across the world in the late twentieth century, led to bursts of property development and market booms. This article examines how this global trend interfaced with local processes in the setting of a secondary metropolis of a developing country, in Metro Cebu, Philippines, and resulted in a property-led development dominated by production of high-end residential real estate commodities, the rise of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…They would be aware of contradictions in government that generate mixed messages; local political elites often support large-scale projects but this may place them at odds with regulatory authorities (Kennedy, 2015; Orueta and Fainstein, 2008). Finally they would know where authorities lack capacity to exert their own imperatives (Sajor, 2003; Shatkin, 2008).…”
Section: Transnational Developersmentioning
confidence: 99%
“…They would be aware of contradictions in government that generate mixed messages; local political elites often support large-scale projects but this may place them at odds with regulatory authorities (Kennedy, 2015; Orueta and Fainstein, 2008). Finally they would know where authorities lack capacity to exert their own imperatives (Sajor, 2003; Shatkin, 2008).…”
Section: Transnational Developersmentioning
confidence: 99%
“…In a comparable study, Cordero and Paus () noted that large amounts of foreign investment in Costa Rica's real estate sector (about 25% of total FDI inflows) contributed to the development of real estate prices over the 2004–2006 period. Sajor () argued that the unprecedented flow of international portfolio investment in real estate facilitated boom and bust property cycles during the 1980s and 1990s globally. A study by Rajan and Siregar () showed that portfolio capital inflows in East Asia were the main factor explaining the rebound in regional growth rates, surges in equity prices, and stabilization of exchange rates during the pre‐crisis boom period (between 1990 and 1996).…”
Section: Related Literaturementioning
confidence: 99%
“…A related point is that a globally operating group of larger property developers may significantly influence the magnitude of peri-urban development in major metropolitan regions (Winarso and Firman, 2002;Sajor, 2003). These private developers tend to have powerful positions, as they own global portfolio's, decide on investments internationally, and are less rooted locally (e.g., Jones, 2009).…”
Section: Flows and Drivers Of Changementioning
confidence: 99%